Denosumab Use in Chronic Kidney Disease Associated Osteoporosis: A Narrative Review - Abduelkarem AR; Guella A; Hamrouni AM; Hassanein MM; Nasr A; Rana O (Dove Medical Press, 2023)
Abduelmula R Abduelkarem,1,2 Adnane Guella,3 Amar M Hamrouni,4 Mohammed M Hassanein,1 Ahmed Nasr,5 Owais Rana6 1Department of Pharmacy Practice and Pharmacotherapeutics, College of Pharmacy, University of Sharjah, Sharjah, United Arab Emirates; 2Research Institute for Medical and Health Sciences, University of Sharjah, Sharjah, United Arab Emirates; 3Department of Nephrology, University Hospital Sharjah, Sharjah, United Arab Emirates; 4Department of Pharmaceutical Sciences, College of Pharmacy, Al Ain University, Al Ain, United Arab Emirates; 5Pharmacy Department, University Hospital Sharjah, Sharjah, United Arab Emirates; 6Department of Internal Medicine, University Hospital Sharjah, Sharjah, United Arab EmiratesCorrespondence: Abduelmula R Abduelkarem, Department of Pharmacy Practice and Pharmacotherapeutics, College of Pharmacy, University of Sharjah, University City Road - University City, PO Box 27272, Sharjah, United Arab Emirates, Tel +97165057443, Email aabdelkarim@sharjah.ac.aeAbstract: Chronic kidney disease (CKD) and hemodialysis (HD) patients have a high incidence of bone disease and increased fracture risk, making effective management of their bone health a clinical challenge. Denosumab, a human monoclonal antibody, has been investigated as a therapeutic option in this patient population. In this review, we summarize the current evidence on the efficacy and safety of denosumab in CKD and HD patients. A comprehensive search of the relevant literature was conducted, including randomized controlled trials, observational studies, and meta-analyses. The findings suggest that denosumab reduces the risk of fractures and improves bone mineral density in all stages of CKD. The results of this review support the use of denosumab as a promising option for managing bone disease in CKD and HD patients.Keywords: denosumab, chronic kidney disease, hemodialysis, bone disease, fracture risk reduction